Singularidades do espaço-tempo em variedades de Weyl - Lobo, Iarley Pereira (2013)
In this paper, we analyze the existence of space-time singularities from the point of view of geodesic incompleteness. We apply this method, also used to prove the wellknown Hawking-Penrose theorems which states that unless the matter content of the Universe present unusual and exotic properties, the general theory of relativity predicts that space-time singularities will develop either in the past of in the future. In this dissertation we regard this question in different context, namely, by considering alternative gravitational theories formulated in a Weyl integrable geometry (WIST). We extend the Hawking-Penrose theorems to this kind of non-riemannian geometry and obtain conditions for escaping the inevitability of space-time singularities. We also consider the issue of changing frames in scalar-tensor theories and provide a geometric overview of Dickes interpretation of Brans-Dicke theory by unifying the treatment of frames in a weylian scenario.